1976
DOI: 10.1039/c39760000673
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour of water in molten LiNO3–KNO3eutectic

Abstract: Contrary to previous reports, the electroreduction of water in nitrate melts appears to be coupled with nitrite reduction, probably involving an autocatalytic mechanism and an adsorbed intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Instead, this reaction involves the reduction of the nitrate ion to form nitrite and hydroxide ions (39,40), i.e. The water wave in molten nitrates is unusual since water is not reduced to hydrogen gas.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this reaction involves the reduction of the nitrate ion to form nitrite and hydroxide ions (39,40), i.e. The water wave in molten nitrates is unusual since water is not reduced to hydrogen gas.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental results do not give any information on the nature of this new mechanism. The chemical reduction of nitrate ions by electrochemically generated hydrated electrons according to Espinola and Jordan (17) or the catalytic process proposed by Levering and co-workers (19) (Eq. [3] and [4]) could be suitable mechanisms.…”
Section: January 1982mentioning
confidence: 99%
“…In the latter media, water yields a reduction wave at a potential 0.4V less cathodic than the nitrate reduction peak (18). Jordan (16,17) attributed the so-called "water wave" to the diffusion controlled reaction NO~-+ H20 + 2e-~ NO2--I-2 OH- [1] Zambonin and co-workers (12) describe the reaction as H20 + e-~=~ 89 Hs + OH- [2] Lovering and co-workers (19) investigated a "nitrite free" nitrate melt and concluded that the presence of some nitrite ions in the melt (generated, for instance, by an initial cathodic scan) is necessary to observe the water reduction wave. They suggest the following mechanism H~O + NOs-+ 2e-:~-2 OH-+ NO- [3] NO-+ NOs-~=~ 2NOs- [4] Considering these reactions, it seemed interesting to investigate the electrochemical behavior of nitrate ions in dry and acidic hydroxide melts.…”
mentioning
confidence: 97%
“…2 5 9 26 or ammonia [see reactions (2) and (19), respectively]. The fact that the post-peak current contributions from water and ammonia are still controlled (almost to a first approximation) by the diffusion of the two species, seems to indicate that reactions (25) and ( 26) are fast and shifted to the right.…”
Section: T H E Post-peak C U R R E N Tmentioning
confidence: 99%
“…In dry melts only reactions (23) and (24) (prevalent) are r e ~p o n s i b l e ~~for the redissolving of the oxide layer and their rates determine the value of current h, in fig.1. In wet melts an additional important chemical contribution to the total dissolution rate from reaction(25). Similarly, reactions(26) or(25) and(26) increase the Na,O dissolution rate when anhydrous or wet ammonia is present in solution.From fig.1and 3 it can be inferred that the post-peak contributions from NH, and H,O are very close to the pre-peak diffusion currents of the two species.…”
mentioning
confidence: 99%